Question #50391

What is consumption function?Suppose the consumption function of a society is as follows: C=100+0.85Y, where C=Total consumption expenditure and Y=Disposable income.

Answer the following questions:

a.What is the autonomous consumption?

b.What is the total consumption when disposable income is 5000?

c.What is induced consumption when disposable income is 8000?

d.Find MPS .Prove that MPC+MPS=1

Answer the following questions:

a.What is the autonomous consumption?

b.What is the total consumption when disposable income is 5000?

c.What is induced consumption when disposable income is 8000?

d.Find MPS .Prove that MPC+MPS=1

Expert's answer

Consumption function is a single mathematical function used to express

consumer spending and could be written as follows:

C = A + MPC * D

where

C = Consumer spending

A = Autonomous consumption, or the level of consumption that would

still exist even if income was $0

MPC = Marginal propensity to consume, which is the ratio of

consumption changes to income changes

D = Real disposable income

a. So, autonomous consumption = A = 100

b. C=100+0.85Y = 100+0.85 * 5000 = 4350

c. Induced consumption is household consumption that varies with

income = MPC * D = 0.85 * 8000 = 6800

d. MPC+MPS=1

MPS = 1 – MPC = 1 – 0.85 = 0.15

We can prove it:

If Yd = C + S, then any change in Yd must resolve a change in C and

some part a change in S.

So we can write:

ΔYd = ΔC + ΔS

If we divide both sides by ΔYd, and we get:

1 = MPC + MPS

consumer spending and could be written as follows:

C = A + MPC * D

where

C = Consumer spending

A = Autonomous consumption, or the level of consumption that would

still exist even if income was $0

MPC = Marginal propensity to consume, which is the ratio of

consumption changes to income changes

D = Real disposable income

a. So, autonomous consumption = A = 100

b. C=100+0.85Y = 100+0.85 * 5000 = 4350

c. Induced consumption is household consumption that varies with

income = MPC * D = 0.85 * 8000 = 6800

d. MPC+MPS=1

MPS = 1 – MPC = 1 – 0.85 = 0.15

We can prove it:

If Yd = C + S, then any change in Yd must resolve a change in C and

some part a change in S.

So we can write:

ΔYd = ΔC + ΔS

If we divide both sides by ΔYd, and we get:

1 = MPC + MPS

## Comments

## Leave a comment